(untitled) (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2024)
Marketing communications is an important part of building a strong brand image and high customer loyalty The aim of this work is to investigate the effectiveness of marketing communications to achieve these objectives using a qualitative approach that includes literature research customer interviews and interviews with marketers The research results show that effective consistent and integrated marketing communications can help create positive brand perceptions and associations in customers thereby encouraging a favorable brand image Marketing communication elements such as loyalty programs sales promotions and post purchase communications are considered the most effective in maintaining customer loyalty In addition digital marketing communications word of mouth WOM and electronic word of mouth eWOM have a significant influence on brand image and customer loyalty Personalization and personalization of marketing communications are also considered important for message relevance customer engagement and strengthening brand relationships However this research also reveals that some customers doubt the credibility of marketing communications and there are customers who are not loyal because of their true loyalty Overall the results of this research highlight the importance of effective and integrated marketing communications tailored to customer preferences and behavior in building a positive brand image and increasing customer loyalty < em>< p>